Fresh frozen plasma transfusion usage and appropriateness in neonatology (Journal of Fatima Jinnah Medical University, 2019)
Background: It is essential that blood and its components should be used appropriately. There are only a few clear indications for transfusing Fresh frozen Plasma (FFP).The British Society of Hematology recommends FFP usage either when the patient is actively bleeding or in patients who are at high bleeding risk and have coagulation profile abnormality with PT (prothrombin time) or aPTT (activated partial thromboplastin time) values significantly above the normal ranges for age and gestation concurrent to invasive procedures, it is also recommended that prophylactic FFP should not be transfused -have minor prolongation of PT/aPTT, even prior to surgery, but it may be considered for surgery to critical sites. This study was conducted to determine the usage and estimate appropriateness of FFP transfusion in neonatology. Subjects and methods: This was a descriptive cross sectional study included all neonates who received FFP from July to Sep 2018. We recorded their demographics, indication for FFP transfusion, hemoglobin, white cell count, platelet count, pretransfusion and post transfusion PT/APTT/INR (international normalized ratio). Neonates whose mothers were on anticoagulants were excluded from the study. Statistical Analysis was done using SPSS 24.Results: Ages ranged from 1 to 28 days. Male: female 1.6:1. 55% FFP were transfused to bleeding neonates while 45% were transfused either for deranged coagulation tests or as pre-procedural prophylaxis. Conclusion: Prophylactic FFP use is very common. Developing awareness among physicians can improve adherence to recommended indications. Studies that would evaluate restrictive vs. liberal FFP use are needed.
Keywords: Fresh frozen plasma, neonates